(untitled) (Nueva Epoca, 2020)
Five years have passed since the civil and commercial code came into effect. This time allows us to take stock of the application of the Code referring to the legal entity and its regulation. A theme that exceeded the regulation imposed by the Nineteenth Code, which contained a concise regulation of both physical and legal persons. The systematization in a g eneral common part of all legal entities has been, without a doubt, a significant advance, as well as the expansion of the enumeration of legal entities. After the enactment of the Civil and Commercial Code, Law 27401 on Criminal Liability of legal persons was enacted, in our opinion it completed the system in the sphere of liability of legal persons However, we ask ourselves, if legal persons respond both civilly and criminally, can they be legitimately active in e xtra-patrimonial or non-patrimonial damages? We intend to analyze the question under the damage regulations incorporated by the CCyCN.